Effect of the aerobic capacity on the validity of the anaerobic threshold for determination of the maximal lactate steady state in cycling - Denadai, B.S. [UNESP] (2004)
The maximal lactate steady state (MLSS) is the highest blood lactate concentration that can be identified as maintaining a steady state during a prolonged submaximal constant workload. The objective of the present study was to analyze the influence of the aerobic capacity on the validity of anaerobic threshold (AT) to estimate the exercise intensity at MLSS (MLSS intensity) during cycling. Ten untrained males (UC) and 9 male endurance cyclists (EC) matched for age, weight and height performed one incremental maximal load test to determine AT and two to four 30-min constant submaximal load tests on a mechanically braked cycle ergometer to determine MLSS and MLSS intensity. AT was determined as the intensity corresponding to 3.5 mM blood lactate. MLSS intensity was defined as the highest workload at which blood lactate concentration did not increase by more than 1 mM between minutes 10 and 30 of the constant workload. MLSS intensity (EC = 282.1 ± 23.8 W; UC = 180.2 ± 24.5 W) and AT (EC = 274.8 ± 24.9 W; UC = 187.2 ± 28.0 W) were significantly higher in trained group. However, there was no significant difference in MLSS between EC (5.0 ± 1.2 mM) and UC (4.9 ± 1.7 mM). The MLSS intensity and AT were not different and significantly correlated in both groups (EC: r = 0.77; UC: r = 0.81). We conclude that MLSS and the validity of AT to estimate MLSS intensity during cycling, analyzed in a cross-sectional design (trained x sedentary), do not depend on the aerobic capacity.